The transition from underwater to surface swimming during the push-off start in competitive swimmers - Trinidad, A.; Veiga Fernandez, S.; Navarro Cabello, E.; Calvo, A. L. (Journal of Human Kinetics, 2020)
+/-The objective of the present study was to analyze (based on gender and the style of swimming) the kinematic parameters of the transition phase between underwater swimming and surface swimming after the push-off start in competitive national swimmers. Seventy-four swimmers participating in the Spanish Swimming Championships were filmed and analyzed by DLT-2D photogrammetry during the start with the push-off in crawl, backstroke and butterfly styles. Between genders there were small differences in the distance and speed of transition. The male swimmers travelled greater distances (0.84 +/- 0.04 vs. 0.66 +/- 0.04 m, Eta2 = 0.05, F = 10.34, p < 0.001) and they were faster (1.59 +/- 0.03 vs. 1.38 +/- 0.03 m/s, Eta2 = 0.08, F = 19.54, p < 0.001) in the transition phase than female swimmers. Among styles there were greater differences in time (Eta2 = 0.47, F = 94.50, p < 0.001) and transition distance (Eta2 = 0.38, F = 67.08, p < 0.001), than in speed (Eta2 = 0.05, F = 5.63, p < 0.001). During the backstroke push-off, swimmers spent more time (0.88 +/- 0.04 s) and distance (1.17 +/- 0.05 m), this being the slowest style (1.37 +/- 0.04 m/s). In butterfly, athletes used less time (0.26 +/- 0.03 s) and distance (0.39 +/- 0.05 m) whereas crawl was the fastest of all (1.57 +/- 0.04 m/s). These results allow the phase of transition from underwater to surface swimming to be characterized and to provide useful data for competitive swimmers and coaches to improve performance.